Ultrasonic characterization and multiscale analysis for the evaluation of dental implant stability: A sensitivity study. (April 2018) - Scala, I.; Rosi, G.; Nguyen, V.-H.; Vayron, R.; Haiat, G.; Seuret, S.; Jaffard, S.; Naili, S.
Highlights: A mechanical modeling to extract information about primary stability of an implant. A complex ultrasonic signal obtained from a probe screwed to the implant. Multifractal analysis has evidenced a signature of the stability. A correlation has been observed between the multifractal signature and the stability. Abstract: With the aim of surgical success, the evaluation of dental implant long-term stability is an important task for dentists. About that, the complexity of the newly formed bone and the complex boundary conditions at the bone-implant interface induce the main difficulties. In this context, for the quantitative evaluation of primary and secondary stabilities of dental implants, ultrasound based techniques have already been proven to be effective. The microstructure, the mechanical properties and the geometry of the bone-implant system affect the ultrasonic response. The aim of this work is to extract relevant information about primary stability from the complex ultrasonic signal obtained from a probe screwed to the implant. To do this, signal processing based on multiscale analysis has been used. The comparison between experimental and numerical results has been carried out, and a correlation has been observed between the multifractal signature and the stability. Furthermore, a sensitivity study has shown that the variation of certain parameters ( i.e. central frequency and trabecular bone density) does not lead to a change in the response.